PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TPS UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V SD NEGERI 007 LUBUK BANGKO. KECAMATAN SEBERIDA KABUPATEN INDRAGIRI HULU - Muhammad Ilham; Mahmud Alpusari; Damanhuri Daud (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrac : The background of the research had been low result student science while overage 68,68 minimum completences criteria( KKM ) 70. The number of the student are 25 student. But only to student to reach ( KKM ) scored 40 %. This research to action research class( are ) the alms to improve grade V student science learning achievement at SD 007 Lubuk Bangko the applicationof the cooperative learn TPS model type to improve grade V students science learning achievement of SD Negeri 007 Lubuk Bangko Kabupaten INHU. This research was conducted 19 march 2015 - 9 april 2015 with contain of two cycles. The nambers of student areb 25 student. Instrument of the recarch contain ( syllabus, RPP, LKS ) this research result of dally test whit average 68,68 %, increased cycle I average 70,88 % . cycle II increased 85,28 %. Process learn teacher on cycle I, meeating I 54,16 % and meating II increased 66,67 %. Cycle II meeting I 83,33% and meeting II increased 91,66%. The result data student analized on cycle I, meeting I 45,83%, and meeting II increased 58,33%, cycle II meeting I 76,16% meeting II. Increased 91,66% from the explanation above shows that. The application of the cooperative learn TPS model type to improve grade V students science learning achievement at SD Negeri 007 Lubuk Bangko kecamatan seberida kabupaten Indragiri Hulu.Key word: Coopertive model tipe TPS. Outcome IPA